Mycobacterium avium subspecies impair dendritic cell maturation. Issue 5 (October 2013) - Basler, Tina; Brumshagen, Christina; Beineke, Andreas; Goethe, Ralph; Bäumer, Wolfgang
Mycobacterium avium ssp. paratuberculosis (MAP) causes Johne's disease, a chronic, granulomatous enteritis of ruminants. Dendritic cells (DC) of the gut are ideally placed to combat invading mycobacteria; however, little is known about their interaction with MAP. Here, we investigated the interaction of MAP and the closely related M. avium ssp. avium (MAA) with murine DC and the effect of infected macrophages on DC maturation. The infection of DC with MAP or MAA induced DC maturation, which differed to that of LPS as maturation was accompanied by higher production of IL-10 and lower production of IL-12. Treatment of maturing DC with supernatants from mycobacteria-infected macrophages resulted in impaired DC maturation, leading to a semi-mature, tolerogenic DC phenotype expressing low levels of MHCII, CD86 and TNF-α after LPS stimulation. Though the cells were not completely differentiated they responded with an increased IL-10 and a decreased IL-12 production. Using recombinant cytokines we provide evidence that the semi-mature DC phenotype results from a combination of secreted cytokines and released antigenic mycobacterial components of the infected macrophage. Our results indicate that MAP and MAA are able to subvert DC function directly by infecting and indirectly via the milieu created by infected macrophages.